Making the lean manufacturing supply chain leap across small and medium scale industries (SMIs) in Malaysia - Ariff, Tasnim Firdaus; Ahmed, Shamsuddin (2005)
The aim of this paper is to present a framework mainly focussing on lean supply chains suitable for the operation of SMIs in Malaysia. This model shall present the strategies to instill supplier capabilities and the supporting activities in creating a lean supply chain across multiple tiers. This paper uses a case study to illustrate its findings based on a medium scale industry in Malaysia. Further empirical research is needed to formulate a research framework that could be used as a generic model for SMIs. The framework is tested and tentative implications are summarized.